Hider, seeker, secret keeper - Kiem, Elizabeth, 1970- (Soho Teen, 2014)
When her friend and chief rival in the Bolshoi Ballet is brutally attacked on the eve of a New York City tour, teenaged Lana Dukovskaya is given her coveted solo--an unlikely stroke of luck that makes Lana the chief suspect in the attack.